2011
DOI: 10.1007/s10822-011-9427-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics and docking simulations as a proof of high flexibility in E. coli FabH and its relevance for accurate inhibitor modeling

Abstract: Bacterial β-ketoacyl-acyl carrier protein synthase III (FabH) has become an attractive target for the development of new antibacterial agents which can overcome the increased resistance of these pathogens to antibiotics in clinical use. Despite several efforts have been dedicated to find inhibitors for this enzyme, it is not a straightforward task, mainly due its high flexibility which makes difficult the structure-based design of FabH inhibitors. Here, we present for the first time a Molecular Dynamics (MD) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…In any event, the current model for type II FA biosynthesis in E. coli needs revision. In addition, these findings have important implications for whether FabH is an effective target for antibiotic intervention (55,(66)(67)(68)(69). At the moment, whether any of the condensing enzymes involved in FA elongation (FabF/B) can substitute for FabH in E. coli is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In any event, the current model for type II FA biosynthesis in E. coli needs revision. In addition, these findings have important implications for whether FabH is an effective target for antibiotic intervention (55,(66)(67)(68)(69). At the moment, whether any of the condensing enzymes involved in FA elongation (FabF/B) can substitute for FabH in E. coli is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Fasoli et al [21] also revealed that the flexibility of subtilisin from Bacillus licheniformis in octane (log P = 4.183) was lower than in acetonitrile (log P =´0.334). As discussing the flexibility of the enzyme, it was worthily noted that enyzme flexibility was usually determined from MD simulations and it is measured by the relative calculated B-factors [22].…”
Section: Effect Of Log P Value Of Organic Solventmentioning
confidence: 99%
“…Knowledge of the kinetics and of the conformational flexibility of an enzyme can significantly contribute to a successful rational drug design [27-29]. Herein we study the molecular basis of PqsD and the HHQ biosynthesis combining experimental and in silico methods.…”
Section: Introductionmentioning
confidence: 99%